Absorption of Electromagnetic Waves by Fe\(_3\)O\(_4\)/Paraffin Composite Materials - Nguyen, Hong Thi Minh; Nguyen, Duy Van; Nguyen, Co Dang; Bui, Tu Dinh; Pham, Thang Duc (Communications in Physics, 2019)
Electromagnetic pollution in general and the harmful effects of microwave radiation in particular on environment is currently in the urgent stage. To eliminate the effect of electromagnetic energy the most common methods relies on the use of absorbing materials with large absorption capacities in wide frequency band. In this paper, we investigate the capability of absorption of electromagnetic waves of Fe3O4 nanoparticles in paraffin basis. The Fe3O4/paraffin composite materials were prepared with a weight ratio of 35%/65%. The dielectric constant (εr) and the magnetic permeability (μr) in the frequency (f) range from 8 to 18 GHz were measured for various sample thicknesses. The results indicated a large dielectric loss and strong thickness dependence of absorption capacity. The maximum absorption coefficient (RL) is of order -13.6 dB, corresponding to the achieved absorbance of 96,9% for the 2.6 mm of sample thickness. The experimental results are consisted with our simulation calculation.